Instabilities and vertical mixing in river plumes: application to the Bay of Biscay - Ayouche, Adam; Carton, Xavier; Charria, Guillaume; Theettens, Sebastien; Ayoub, Nadia (Geophysical and astrophysical fluid dynamics, 2020)
In the Bay of Biscay (north-east Atlantic), long-living eddies and the frontal activity that they induce substantially contribute to mesoscale and submesoscale dynamics. Tides and river plumes also contribute to frontal activity. Biological productivity is sensitive to river plume fronts and to external forcings (tides and wind). Considering the importance of river plumes, we study here the structure, stability and vertical mixing processes in such river plumes (similar to those generated by the Gironde river). Restratification budget is considered here for evaluating stirring (frontogenetic/frontolytic) or vertical mixing (parametrised here from Ertel potential vorticity mixing) processes. Using high-resolution idealised numerical simulations, we analyse the evolution of the bulge and of the coastal part of this plume and we conduct sensitivity experiments to the river discharge, to southwesterly winds and to M2 tides. The bulge and the coastal current are stable (unstable) in case of moderate (high) river discharge, due to mixed barotropic/baroclinic instabilities. In the unstable case, near surface symmetric and vertical shear instabilities develop in the coastal current and in the core of the bulge where the Rossby number is large. When southwesterly winds blow, the river plume is squeezed near the coast by Ekman transport. The river plume is then subject to frontal symmetric, baroclinic, barotropic and vertical shear instabilities in the coastal part, north of the estuary (its far field). Conversely, in the presence of M2 tides, the river plume is barotropically, baroclinically and symmetrically unstable in its near field. Interior vertical mixing is induced by advective (stirring) and frontogenetic processes. Frontogenesis is dominant in the far-field (in the presence of southwesterlies) or in the near-field (when M2 tide is active). Frontogenesis is important in the far-field region in unforced river plumes (both with moderate and high river discharges). Potential vorticity is eroded in the far-field when southwesterlies blow. This is primarily due to the frictional processes which are dominant at the surface. This study has identified the instabilities which affect a river plume in different cases, and the local turbulent processes which alter the stratification.